1980
DOI: 10.1111/j.1095-8649.1980.tb02755.x
|View full text |Cite
|
Sign up to set email alerts
|

The detection of dissolved amino acids by the Atlantic cod, Gadus morhua L.

Abstract: A classical conditioning technique was employed with cod, Gadus morhua L., to determine thresholds for the detection of the L-forms of some a amino acids which are thought to be attractants or feeding stimulants for fish. The amino acids investigated, in order of effectiveness, were tyrosine, cysteine, phenylalanine, glycine and methionine with mean threshold response levels ranging from 2.5 x lo-% to 7.4 x lo-". Histidine and lysine resulted in similar thresholds with a mean value of approximately 3 x lo-% wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…In a study using a conditioning technique, Johnstone (1980) found that the detection thresholds of cod, Gudus morhuu L., to the most effective amino acids tested ranged from 2.5 x lo-' to 7-4 x l o -* M. Johnstone (1980) also gives a summary of comparable threshold determinations obtained for other species. With the exception of the threshold value for L-alanine (10 M) for channel catfish, Ictulurus punctutus Rafinesque, these thresholds are all more than two orders of magnitude higher than the value we found for food-deprived sablefish.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In a study using a conditioning technique, Johnstone (1980) found that the detection thresholds of cod, Gudus morhuu L., to the most effective amino acids tested ranged from 2.5 x lo-' to 7-4 x l o -* M. Johnstone (1980) also gives a summary of comparable threshold determinations obtained for other species. With the exception of the threshold value for L-alanine (10 M) for channel catfish, Ictulurus punctutus Rafinesque, these thresholds are all more than two orders of magnitude higher than the value we found for food-deprived sablefish.…”
Section: Discussionmentioning
confidence: 95%
“…The active space of a bait source is an essential parameter in stock assessment models developed for estimation of fish populations, such as sablefish, that are harvested mainly by baited gears (McQuinn et al, 1988). Such information can also provide a better understanding of the process by which baited gears catch fish, and is important for improvements in gear selectivity (Lpkkeborg & Bjordal, 1992) and artificial bait development (Johnstone, 1980;L~kkeborg, 1990).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although care should be taken with generalisations, some features of each of the systems seem to be consistent over a wide range of species. Based on its lower detection thresholds (Johnstone 1980;Ishida and Kobayashi 1992), olfaction is believed to initiate food search behaviour for a wide variety of odours, while the gustatory system seems to be more selective and provides the final sensory evaluation (i.e. odours may trigger food search, however the gustatory system may reject the object after tasting it) (Kasumyan and Døving 2003).…”
Section: Chemoreceptionmentioning
confidence: 99%
“…There is a proportional increase in the concentration of stimulus required for detection as the background concentration rises (Johnstone, 1980). More studies on the effects of prolonged subthreshold-stimulus exposure are required.…”
Section: Released Behaviorsmentioning
confidence: 99%